2014
DOI: 10.1074/jbc.m113.455766
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 Induces Up-regulation of Endothelial Cell Claudin-5 through Activation of FoxO1

Abstract: Background: IL-4 protects vascular endothelial cells (ECs) from complement-mediated junctional injury and cytotoxicity. Results: IL-4 induces up-regulated expression of junctional claudin-5 through STAT6 and FoxO1. Claudin-5 up-regulation contributes to, but is not sufficient, for protection. Conclusion: IL-4-induced claudin-5 is an important component in protection of ECs from complement. Significance: Regulation of claudin-5 expression may play a role controlling EC inflammatory injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 37 publications
0
32
1
Order By: Relevance
“…The molecular mechanism of this effect is unclear at present, and it does not involve induction of the Serpin inhibitor Spi6. Notably, IL-4-induced phosphorylation of another FoxO family member, FoxO1, has been shown to prevent EC cytolysis by up-regulating claudin-5 expression and junction tightness (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanism of this effect is unclear at present, and it does not involve induction of the Serpin inhibitor Spi6. Notably, IL-4-induced phosphorylation of another FoxO family member, FoxO1, has been shown to prevent EC cytolysis by up-regulating claudin-5 expression and junction tightness (31).…”
Section: Discussionmentioning
confidence: 99%
“…7G), indicating that perforin-induced osmotic lysis is only partially inhibited by CD31 signals. FoxO3, which has been implicated in osmotic lysis (31), localized to the nucleus only in mock-transduced but not in CD31-expressing MIN6 cells after incubation with CTLs (Fig. 7H).…”
Section: Cd31 Expression Confers Resistance To Cytolysis By Alloreactmentioning
confidence: 99%
“…In our previous studies, we have also found that the protection induced with IL-4 and IL-13 was intrinsic and required activation of fatty acid and phospholipid synthesis, including cardiolipin, and preservation of mitochondrial integrity [3,4]. In addition, we found that IL-4 induced up-regulation of the junction protein claudin-5, which contributed to EC protection from complement injury [5].…”
Section: Introductionmentioning
confidence: 73%
“…[167][168][169] New intracellular mechanisms that mediate protection from complement injury include increased expression of claudin-5, and endothelial induction of adenoIL-4; IL-4 is a potent inducer of protection . [170][171][172] Importantly, this protection is associated with maintenance of mitochondrial morphology and membrane potential and is not related to upregulation of complement-regulatory proteins.…”
Section: Survival With Immunosuppressive Therapy (Ref)mentioning
confidence: 98%